Acceptability of an indigenous Philippine berry [Lipote, Syzygium curranii (C.B.Rob.) Merr., Myrtaceae] as an entrepreneurial product - Reyes, Editha Guevarra (2004)
This study was designed to determine the acceptability of processed lipote as an entrepreneurial product based on appearance, palatability and general acceptability. The respondents consisted of 12 laboratory panelists (food technology students) and 100 consumers who were purposively chosen from the CvSU Home Economics, Vocational and Technical Education Department (HEVTED) population. Score sheets using four-point Hedonic scale and a questionnaire were given to the respondents to gather data. Age, gender, educational attainment, family income, food and entrepreneurial orientation were factors found to be correlated with acceptability. However, coefficients of correlation were weak to be predictive. There were significant differences in the perceived acceptability of processed lipote product between the two types of respondents. All processed lipote products were found acceptable in terms of appearance, palatability and general acceptability. However, jelly was found to be more acceptable than jam and juice. Tertiary Home Economics should incorporate product development using indigenous fruits in the curriculum as part of entrepreneurship to create more livelihood opportunities, thereby improving family well-being.